Characterization and Holographic study of nanostructure Copper Selenide thin films grown at room temperature. (2020) - Malekar, V.P.; Gangawane, S.A.; Fulari, V.J.
Abstract: Nanostructure Copper Chalcogenide thin films can be prepared using electrodeposition technique. The structural, morphological and surface wettability properties of the as deposited Copper Selenide thin films have been studied using XRD, SEM and contact angle measurement Optical band gap energy (Eg value) for Copper Selenide thin films ranges from 2.4 eV to 2.6 eV. FT-Raman and FT-IR spectral properties of the deposited films have been studied by FT Raman and FT-IR spectrophotometer. Using as deposited holographic thin films fringe width, thickness of thin film, stress to substrate and mass deposited can be calculated. It is observed that, increase in deposition time thickness of thin film and mass deposited increases but fringe width as well as stress to substrate decreases